Understanding quality of life in pediatric cystic fibrosis: insights from a multicenter cohort study across Colombia (2026)
Background: Health-related quality of life (HRQoL) in cystic fibrosis (CF) reflects the interplay of clinical, functional, and contextual determinants. While pulmonary function, nutritional status, exacerbations, and treatment burden are well-established contributors, less is known about how the residential environment—including altitude, cultural context, and access to care—modulates perceived well-being in Latin American pediatric populations. Methods: We conducted a prospective multicenter cohort sub-analysis of 94 children and adolescents with CF aged 6–18 years, followed for 12 months across four Colombian cities located at different altitudes. HRQoL was assessed using age-specific CFQ-R instruments and the caregiver-proxy version. Complementary measures included CF-POP and CF-ABLE scores, spirometry, nutritional indicators, six-minute walk test (6MWT) performance, hospitalizations, and systemic antibiotic use. Between-group comparisons were performed with non-parametric tests. Multivariable linear and quantile regression models were used to identify independent correlates of HRQoL.